PENERAPAN P5: KOLABORASI PELAJARAN ILMU SOSIAL EKONOMI SAINS DAN SENI BUDAYA PADA KURIKULUM MERDEKA - Aditya, Mega Cantik Putri (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The purpose of this study was to find out the implementation of the independent curriculum for one of the private high schools in Pontianak City. The implementation of the independent curriculum at SMAS Kemala Bhayangkari builds the character and competence of students through strengthening the Pancasila student profile project (P5). The P5 embodiment collaborates Economics and Cultural Arts lessons in phase E (grade 10). The qualitative research method is descriptive type. Data collection techniques are observation, interviews and documentation. The results in this research are the application of the independent curriculum at SMAS Kemala Bhayangkari only in the lowest grade level, namely grade 10. The implementation of the independent curriculum was very different before its implementation, where the learning process of the independent curriculum dominantly used project activities by students. SMAS Kemala Bhayangkari only uses 3 projects, including Unity in Diversity, Entrepreneurship and Building Soul and Body. Each project has outcomes in the form of knowledge and creative work or practice. The implementation of the project has an impact on schools, teachers and students. The impact is that students are more active, teachers are more innovative and schools are always ready to conduct training and upgrade teacher knowledge.